Use of force by police officers in Bosnia and Herzegovina - Gojko Šetka; Dragomir Jovičić (Revija za kriminologiju i krivično pravo)
The police indisputably represent one of the most important and, for citizens, the most visible state body. The nature of police activities places it within the realm of concern for every citizen, regardless of their differences. The main reason for this is certainly the powers that the state, through the legislative framework, has conferred upon the police as a specialized state body, enabling the police to effectively carry out their duties. The police are a particularly interesting state body given their authority to apply force against citizens, but strictly in cases prescribed by laws and regulations. It is imperative that police officers can apply force solely in accordance with the prescribed procedures. Since the application of force produces consequences that cannot be subsequently eliminated, it is crucial for police officers to know the legal basis for the use of force, as well as the methods for its use. In this work, by employing scientific methods and collecting data through interviews with police officers from all levels of the police system, we aimed to attain insights into the situation in the area of the application of force by police officers in Bosnia and Herzegovina.